Lie Symmetries, Conservation Laws, Optimal System and Similarity Reductions of (2+1)-Dimensional Fractional Hirota-Maccari System (Journal of Partial Differential Equations, 2025)
In this paper, Lie symmetry analysis method is applied to one type of mathematical physics equations named the (2+1)-dimensional fractional Hirota-Maccari system. All Lie symmetries and the corresponding conserved vectors for the system areobtained. The one-dimensional optimal system is utilized to reduce the aimed equations with Riemann-Liouville fractional derivative to the (1+1)-dimensional fractionalpartial differential equations with Erdélyi-Kober fractional derivative.
Keywords: Lie symmetry analysis; fractional Hirota-Maccari system; one-dimensional optimal system; conservation laws.